Ocular Surface Evaluation in Allogenic Hematopoietic Stem Cell Transplantation Patients. Issue 5 (September 2014) - Vanathi, Murugesan; Kashyap, Seema; Khan, Rehan; Seth, Tulika; Mishra, Pravas; Mahapatra, Manoranjan; Tandon, Radhika
Purpose: To evaluate ocular surface of chronic graft versus host disease (GVHD) patients in allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: Cross-sectional study of allo-HSCT patients. Data recorded included Ocular Surface Disease Index (OSDI) score, fluorescein tear break-up time (FTBUT), Schirmer I test, ocular surface staining, dry eye severity, and conjunctival impression cytology (CIC). Results: Of 40 allo-HSCT patients (mean age 25.7 ± 11.03 years) studied, dry eye disease was noted in 30%. The OSDI was mild in 16.67%, moderate in 45.83%, and severe in 20.83% ocular GVHD (oGVHD) eyes; mild in 94.64%, moderate in 5.36% non-oGVHD eyes (p<0.001). The FTBUT was ≤5 seconds in 45.83%, >5 seconds in 54.17% of eyes with chronic oGVHD. Schirmer I test score was ≤5 mm in 58.33% of eyes with oGVHD. Conjunctival staining score was <3 in 25%, ≥3 in 75% of oGVHD eyes. Corneal staining score of <3 in 79.17%, ≥3 in 20.83% was seen in oGVHD eyes. Chronic oGVHD was seen in 24 eyes, with dry eye severity of level 3 in 17.5%, level 2 in 2.5%, level 1 in 10%. The CIC was abnormal in 75% with altered morphology seen in 22 eyes with oGVHD (91.7%) and 38 eyes without oGVHD (67.9%) (p = 0.024). Conclusions: Significant ocular surface changes occur due to chronic oGVHD in allo-HSCT patients. The OSDI score, corneal involvement, and Schirmer I test are indicative of ocular morbidity in post allo-HSCT eyes. Conjunctival impression cytology abnormality is also seen in eyes without oGVHD.